A Multicenter Retrospective Study of Gemcitabine Plus Nab-Paclitaxel for Elderly Patients With Advanced Pancreatic Cancer. Issue 2 (February 2020) - Kobayashi, Satoshi; Ueno, Makoto; Ikeda, Masafumi; Ozaka, Masato; Sano, Yusuke; Hirotani, Akane; Tozuka, Yuichiro; Fukushima, Taito; Tezuka, Shun; Moriya, Satoshi; Umemoto, Kumiko; Watanabe, Kazuo; et al.
Abstract : Objectives: This study aimed to assess the lesser known therapeutic benefit, particularly safety and effectiveness of gemcitabine plus nab-paclitaxel (GnP) treatment in elderly patients with advanced pancreatic cancer. Methods: We retrospectively enrolled advanced pancreatic cancer patients aged ≥75 years who received GnP as first-line treatment between December 2014 and December 2016. We assessed survival, adverse events, and early treatment discontinuation. Results: The cohort comprised 116 patients (median age, 77 [range, 75–84] years). The overall survival and progression-free survival were 21.8 and 12.1 months in patients with locally advanced cancer and 13.3 and 5.9 months, in patients with metastasis, respectively. The response and disease control rates were 31% and 81%, respectively. Within the first 2 months of treatment, grade 4 hematological and grade 3–4 nonhematological toxicities occurred in 10 and 23 patients, respectively. Early discontinuation due to adverse events occurred in 12 patients; the associated risk factors were age ≥80 years (odds ratio, 9.43) and serum albumin level <3.5 g/dL (odds ratio, 5.12). Conclusions: In selected patients aged ≥75 years, GnP showed acceptable toxicities and effectiveness. However, patients aged ≥80 years and those with serum albumin levels <3.5 g/dL should be carefully assessed for treatment eligibility.